Evaluating the impact of autonomous material handling on the performance of production system: a simulation approach - Purwaningsih, Ratna; Shintyastuti, Annisa Rahma; Arvianto, Ary; Hapsari, Chaterine Alvina Prima; Putri, Ade Aisyah Arifna; Dzulfikar, Rifki Daris (SINERGI, 2025)
In developing countries, low employment rates lead to manual material handling due to low labor costs. This article analyzes the impact of transitioning from semi-manual to fully automatic material handling systems by replacing the hand pallet system with AGV for transporting materials on the production floor. A simulation model was created to evaluate the impact of the transition on cost and quality. The model focuses on production lines with predetermined pathways and fixed working hours for workstations. The discrete event simulation was developed using ExtendSim. Queuing theory model is employed to assess the utilization of resources within the system. Three scenarios are developed: a human system, systems with 2 AGVs, and 3 AGVs.The findings suggest that systems with AGVs surpass human-operated systems in terms of system reliability, cost-effectiveness, and product excellence. The findings provide essential insights for management decision-making, specifically for deterministic production lines. The research findings emphasize the possibility of significant enhancements in production system performance by implementing autonomous material handling.